Erratum to: Seeding the galactic centre gas stream: gravitational instabilities set the initial conditions for the formation of protocluster clouds - Henshaw, Jonathan D.; Longmore, Steven N.; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society. Letters, 2016)
© 2016 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Societyerrata, addenda, stars: formation, ISM: clouds, ISM: kinematics and dynamics, ISM: structure, Galaxy: centre, Galaxy: kinematics and dynamics...The paper ‘Seeding the Galactic Centre gas stream: gravitational instabilities set the initial conditions for the formation of protocluster clouds’ was originally published in MNRAS, 463, L122 (2016).After online publication of Henshaw, Longmore & Kruijssen (2016), we discovered a number of errors in Table 1. Due to an integer division error, the number densities presented are a factor of 4/3 greater than they should be. Additionally, the tabulated densities refer to atomic hydrogen number densities (μ = 1.4), not molecular hydrogen number densities (μ = 2.8, as claimed). These two errors propagated into the computation of the free-fall times. To summarize, the number densities and free-fall...
Gesehen am 24.10.2017